Does monetary union membership affect convergence in the European Union? - Dzenita Siljak; Sándor Gyula Nagy (DANUBE: Law, Economics and Social Issues Review, 2021)
The objective of the article is to investigate the effects of the stage of integration on convergence in the European Union. The relationships between the selected macroeconomic variables and per capita GDP growth rate are econometrically tested for the period 2004-2018 and three sub-periods: the pre-crisis period 2004-2008, the crisis period 2009-2013, and the post-crisis period 2014-2018. Convergence is estimated using ordinary least squares (OLS) semi-log regression based on cross-sectional data. The findings show that convergence rates range between 1.9 percent and 4.8 percent. The positive effects of deeper integration are identified, as well as the negative effects of the 2008/2009 crisis. The empirical results suggest that the selected variables have an impact on the per capita GDP growth rate in at least one analyzed period.
Keywords: 330; Beta Convergence; Monetary Union; European Union; Optimum Currency Area Theory; Financial Crisis